Advantages of ion-exchange chromatography for oligonucleotide analysis. (May 2011) - Cook, Ken; Thayer, Jim
The rapid development of therapeutic oligonucleotides (ONs) has created a need for in-depth characterization of ONs, beyond previous requirements. The natural migration to LC––MS requires the use of chromatography with MS-compatible eluents to introduce the large, highly charged biopolymers into the mass spectrometer. Most frequently this employs ion-pair reversed-phase liquid chromatography, which may leave gaps in the characterization, but these can be filled with the use of high-resolution ion-exchange chromatography. Several classes of isobaric isomers are among the impurities that will require further separation prior to MS analysis. This review shows how the use of ion exchange as an additional orthogonal analytical method can be used as standalone or interfaced with MS to achieve the highest possible analytical coverage in the characterization and quantification of impurities present in single- and double-stranded ON formulations. Some of these techniques have been in use for some time and the importance of others is just being recognized.